7 Kebiasaan Anak Indonesia Hebat Mendidik Karakter Anak Sejak Dini - Sulastya Ningish; Nurul Aini MM Sodik; Tiansi Mustapa; Nuraini S. Lawadjo; Faujia Polamolo (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
Character building in early childhood plays a crucial role in shaping a generation that is well-mannered, disciplined, and accustomed to living a healthy lifestyle. One of the government’s initiatives in this effort is the national program 7 Habits of Great Indonesian Children, which includes the habits of waking up early, practicing worship, exercising, consuming nutritious food, enjoying learning, engaging in community life, and sleeping on time. This program is designed to instill positive values in children in a structured and continuous manner from an early age. The socialization activity carried out at TK Agropolitan, Bone Bolango Regency, aimed to help teachers and the community understand how to implement these seven habits in children’s daily routines. The activity began with initial observation, preparation of materials, and coordination with the school and village authorities, followed by the delivery of materials through panel presentations and discussions. The results show that applying these seven habits can strengthen children’s character development, particularly in independence, discipline, and social-emotional skills. However, implementation still faces several challenges, including limited parental support, insufficient facilities, and the negative impacts of technology. This socialization activity highlights the importance of collaboration among parents, teachers, and the surrounding community to ensure sustainable character development in children.